Prospective clinical trial of polyethylene fiber ribbon-reinforced, resin composite post-core buildup restorations - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2007)
The aim of this prospective clinical trial was to determine the outcome of polyethylene fiber ribbon-reinforced, resin composite post-and-core restorations used as endodontic buildups to support all-ceramic crowns. A total of 42 teeth (31 anterior, 11 posterior) with a mean follow-up time of 35.85 months (range, 10 to 73 months) were treated with 3-mm-wide polyethylene fiber ribbon-reinforced resin composite as post-and-core material. The posts and cores were assessed by clinical and radiographic examination. During the evaluation period, only 1 dentin-cement failure was observed as a post dislodgement after 11 months of clinical service. Performance of polyethylene fiber ribbon post and resin composite core foundation restorations provided clinically satisfactory support for all-ceramic crowns.